Efektifitas Inseminasi Buatan Pada Sapi Potong Menggunakan Semen Cair - Nelly Kusrianty; Mirajuddin Mirajuddin; Awalludin Awalludin (Mitra Sains, 2016)
This research aims to determine the level of effectiveness of artificial insemination in Locally bull using liquid cement based on conception rate (CR) and service per conception (S/C) in Kab. Mamuju Utara Sulawesi Barat Province. And to study the economic value of artificia insemination using liquid semen on local bull in Kab. Mamuju Utara Sulawesi Barat Province. This research used survey methode and record 109 cattle that have been inseminated from 36 farmer in Kabupaten Mamuju Utara Sulawesi Barat Province. Liquid semen that used is from Simental, Limosin and Bali breed. The data is analised by deskripted statistic. Result of this research is shown 93,3 % (94 : 109 cattle) or S/C is 1,08. The cost of using liquid semen on the implemantation AI per pregnancy is Rp. 178.200,- lower178% compared by AI using a frozen semen. Further research is needed about AI using a liquid semen from local region.